2009
DOI: 10.1017/s0016756809006487
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope fluctuations of terrestrial organic matter for the Upper Cretaceous (Cenomanian–Santonian) in the Obira area of Hokkaido, Japan

Abstract: Stratigraphic fluctuations of carbon isotope values of terrestrial organic matter within the Upper Cretaceous (Cenomanian-Santonian) sequence in the Obira area of Hokkaido, Japan, record distinctive δ 13 C fluctuations for the Cenomanian-Turonian boundary, the Middle Turonian, the upper Turonian-lower Coniacian, and the Santonian. A biostratigraphic framework of the agediagnostic taxa (ammonoids, bivalves and planktic foraminifers) indicates that these δ 13 C fluctuation events are comparable with those record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 44 publications
4
41
0
Order By: Relevance
“…Hasegawa (1997) discussed the resemblance between the δ 13 C curves for marine carbonates and those for terrestrial organic matter, and concluded that the δ 13 C stratigraphy of terrestrial organic matter provides a reliable tool for correlation with the marine carbonates. Recently, Uramoto et al (2009) supported the usefulness of this tool for correlation and indicated that δ 13 C fluctuations of terrestrial organic matter reflected the global isotopic patterns in the carbon reservoir of the ocean-atmosphere-terrestrial biosphere system. The δ 13 C-based correlations first require, however, determination of the approximate geological ages, based usually on biostratigraphy and complete stratigraphic successions.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Hasegawa (1997) discussed the resemblance between the δ 13 C curves for marine carbonates and those for terrestrial organic matter, and concluded that the δ 13 C stratigraphy of terrestrial organic matter provides a reliable tool for correlation with the marine carbonates. Recently, Uramoto et al (2009) supported the usefulness of this tool for correlation and indicated that δ 13 C fluctuations of terrestrial organic matter reflected the global isotopic patterns in the carbon reservoir of the ocean-atmosphere-terrestrial biosphere system. The δ 13 C-based correlations first require, however, determination of the approximate geological ages, based usually on biostratigraphy and complete stratigraphic successions.…”
Section: Introductionmentioning
confidence: 89%
“…The Hydrogen Index (HI) is the ra- Haboro R. Haboro R. The study areas. The northern rectangle is the Haboro area, the southern area is the Obira area, the middle rectangle with dashed line (a) is the Kotanbetsu area studied by Takashima et al (2010), and the southern rectangle with dashed line (b) is the area studied by Uramoto et al (2007Uramoto et al ( , 2009). (C) Geological map of the Haboro area.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations